THE INFLUENCE OF TRUST, SECURITY AND SERVICE QUALITY TOWARD PURCHASE DECISION AT LAZADA - PRASETYO, KURNIANTO AJI (INDONESIAN RESEARCH SOCIETY, 2018)
The purpose of this study is to find out and analyze customer trust, service, and servicequality on purchasing decisions at Lazada.co.id. Sample in this study there are 120respondents who are customers at Lazada.co.id. Convenience sampling method indetermining the sample of this study. Data were analyzed using multiple regression withSPSS version 25 statistical software. The results of this study indicate that, (1) Customertrust in the purchase results at Lazada.co.id. (2) Security of the purchase results atLazada.co.id. (3) Positive service quality for purchasing decisions at Lazada